Diversity, conservation, potential uses, and alien species of lowland plants of Batang Toru, Sumatra, Indonesia - Hirmas F. Putra; Wendy A. Mustaqim (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putra HF, Mustaqim WA. 2021. Diversity, conservation, potential uses, and alien species of lowland plants of Batang Toru, Sumatra, Indonesia. Biodiversitas 22: 1580-1591. A recent field inventory of lowland Sumatran plant diversity was carried out in two close sites of forest patches in the Batang Toru area. These are Muara Upu Swamp Forest and Simulak Anjing Hill Forest. This study aimed to investigate the species composition of two isolated lowland Sumatran forest patches on the west coast of the northern part of the island. The total number of species recorded was 181 species with 131 species known from Simulak Anjing Hill Forest, 54 from Muara Upu Swamp Forest, and only three species recorded from both sites. There are three species endemic to Sumatra, seven species listed as threatened according to the IUCN Red List, one species protected by the Indonesian government, and two are important records for Sumatra. Compared to the published literature, 88 species have been reported to have one or more uses, with 63 species have been used as the source of medicines, 19 as sources of fibers, 18 as the source of vegetables, and several other uses. Sixteen alien species were recorded including four species categorized as 100 world’s worst invasive species. It can be concluded that both areas are a home for important lowland plants of Sumatra as indicated by the presence of threatened, endemic, or poorly documented species. Besides that, there is also a need for concern about the presence of potential invasive alien species.